2020
DOI: 10.5614/j.eng.technol.sci.2020.52.2.6
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Microplastics in Beach Sand in Tien Giang Province and Vung Tau City, Vietnam

Abstract: Microplastics threaten the ecosystem because of undesirable properties such as non-biodegradability, easy-to-absorb persistant organic compounds, etc. They are found worldwide in marine, fresh water and beach sand environments. In this study, microplastics in beach sand samples from two sites in Tien Giang province and two sites in Vung Tau city were investigated. The results showed that the microplastics amount was 0 to 295 pieces/kg dry sand and they mainly distributed near estuarine areas. Microplastics wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 12 publications
2
4
1
5
Order By: Relevance
“…In addition, sites 1, 2, and 4 were constructed with stone embankments to prevent erosion, leading to more microplastic accumulation than other sites. The results showed some similarities to the research in the same region: Tien Giang and Vung Tau (Hien et al 2020). Microplastics in both investigations shared some common characteristics in terms of the distribution, the chemical composition of the plastic.…”
Section: Interpretations Of Microplastics Origin In Sand Samplessupporting
confidence: 76%
See 1 more Smart Citation
“…In addition, sites 1, 2, and 4 were constructed with stone embankments to prevent erosion, leading to more microplastic accumulation than other sites. The results showed some similarities to the research in the same region: Tien Giang and Vung Tau (Hien et al 2020). Microplastics in both investigations shared some common characteristics in terms of the distribution, the chemical composition of the plastic.…”
Section: Interpretations Of Microplastics Origin In Sand Samplessupporting
confidence: 76%
“…The impact of coastal commercial tourism on sampling sites was also surveyed, the results showed that in the bathing sites attracting many tourists. The number of microplastics observed was signi cantly higher than the deserted areas, steep beaches (Yu et al 2016;Hien et al 2020). This difference can be explained by the application of different methods of sampling and separating microplastics as well as how microplastics are identi ed (Song et al 2015).…”
Section: Introductionmentioning
confidence: 94%
“…With respect to firm types, one of the areas that have received relatively less attention within the research agenda pertains to the role of small and medium enterprises (SMEs) in CSR in Vietnam. In particular, only five articles in our sample specifically investigated CSR in SMEs (Malesky and Taussig, 2017;Nhat Minh and Bich-Ngoc Thi, 2020; Phan Van and Podruzsik, 2018;Tran and Jeppesen, 2016;Van and Nguyen, 2019) and one article focused on CSR in the context of family firms (Hien et al, 2020). According to Jamali et al (2017a), this may suggest a sceptical view among scholars that the engagement of Vietnamese SMEs with social and environmental standards is spontaneous and symbolic of masking and mitigating their noncompliance with fundamental principles and basic tenets of CSR.…”
Section: Corporate Social Responsibilitymentioning
confidence: 98%
“…Corresponding to Table 2, the second most noticeable sector was the textile, garment and footwear industries (12%), followed by tourism and hospitality (10%). These findings are not surprising because these industries, despite being dominant contributors to the country's high growing export-oriented economy, have been criticized for their heavy use of labour (Nayak et al, 2019), enormous plastic waste footprint (Hien et al, 2020) and toxic chemicals discharged into the environment (Phan et al, 2020;Vuong et al, 2021). Therefore, firms operating in these sectors have faced market-driven pressures to implement green practices and adopt CSR-oriented standards to cope with progressive customer demand and trade barriers when trying to integrate into the international markets.…”
Section: Distribution By Industrymentioning
confidence: 99%
“…Các nghiên cứu gần đây về phân bố hạt vi nhựa tại Việt Nam cho thấy môi trường nước các kênh rạch gần các nhà máy trên sông Sài Gòn bị nhiễm bẩn các loại hạt vi nhựa có nguồn gốc từ dệt may [15]. Mức độ nhiễm bẩn vi nhựa trong cát bãi biển tại khu vực thành phố Vũng Tàu và huyện Gò Công, tỉnh Tiền Giang cũng ở mức khá cao, với thành phần chủ yếu là các loại nhựa Polyethylene, Polypropylene, Polystyren [16]. Tuy nhiên, các nghiên cứu về nhiễm bẩn hạt vi nhựa trong trầm tích đáy biển còn khá hạn chế, đặc biệt tại các vũng vịnh ven biển.…”
Section: Mở đầUunclassified